2009
DOI: 10.1111/j.1365-2958.2009.06607.x
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial transport and folding of an autotransporter virulence protein during outer membrane secretion

Abstract: We introduced pairs of cysteine residues into the passenger sequence of pertactin, an AT virulence protein from Bordetella pertussis, and show that OM secretion of the passenger domain stalls due to the formation of a disulphide bond. We further show that the C-terminus of the pertactin passenger domain b-helix crosses the OM first, followed by the N-terminal portions of the virulence protein. In vivo proteolytic digestion shows that the C-terminus is exposed to the extracellular milieu during stalling, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
123
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 24 publications
3
123
0
Order By: Relevance
“…This would be expected for a sequential role of the aromatic residues in the core during the C-to N-terminal folding of the ␤-helix region at the cell surface after a hairpin in the ␤-domain is formed. In accordance with this supposition, for an intermediate of pertactin that was stalled during translocation halfway across the passenger domain, it was shown that the C terminus had crossed the OM (27).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This would be expected for a sequential role of the aromatic residues in the core during the C-to N-terminal folding of the ␤-helix region at the cell surface after a hairpin in the ␤-domain is formed. In accordance with this supposition, for an intermediate of pertactin that was stalled during translocation halfway across the passenger domain, it was shown that the C terminus had crossed the OM (27).…”
Section: Discussionmentioning
confidence: 59%
“…However, most of the available evidence suggests that translocation of the passenger is a vectorial process in which the ␤-domain functions as a protein-conducting channel (2, 3). Recent in vitro unfolding/refolding studies revealed that the pertactin ␤-helix refolds to native protein via an intermediate state with a folded C terminus and unfolded N terminus (20,27). In Hbp, the Trp 1015 residue is located in the cap region that folds to cover the C-terminal end of the ␤-helical stem of the passenger (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating this relationship between the folding and secretion of AT passenger domains have largely focused on disulfide bond formation during transit through the periplasm, between exogenous Cys residues introduced into passenger domains (20,28), or between Cys residues within heterologous passenger domains (29 -36). Although the translocation of sizable folded domains comprising disulfidebonded segments of heterologous passenger domains was reported (30 -32), a greater number of studies have demonstrated that periplasmic formation of either long disulfidebonded loops or tightly folded/rigid structures is incompatible with OM translocation/secretion of AT passenger domains (20,28,29,(33)(34)(35)(36). These dichotomous sets of studies have given rise to two mechanistic models of AT biogenesis, one proposing that passenger domain translocation occurs through a folded AT ␤-barrel pore, and the other proposing BamA as an accessory factor mediating passenger translocation before the ␤-domain adopts a final folded conformation.…”
mentioning
confidence: 99%
“…Usually, the ␤-helix forms a backbone to which additional, functional subdomains are attached. This ␤-helical structure is capped by a C-terminal region, which emerges into the medium first (15). This region forms a structure unique to the AT family and is known as the junction or "autochaperone" (AC) due to its inferred role in folding the entire passenger.…”
mentioning
confidence: 99%